New insights into the anticancer effects of Polycladia crinita aqueous extract and its selenium nanoformulation against the solid Ehrlich carcinoma model in mice via VEGF, notch 1, NF-кB, cyclin D1, and caspase 3 signaling pathway - Alotaibi, Badriyah S.; El-Masry, Thanaa A.; Selim, Hend; El-Bouseary, Maisra M.; El-Sheekh, Mostafa M.; Makhlof, Mofida E. M.; El-Nagar, Maysa M. F. (Frontiers in Pharmacology, 2024)
Background: Phaeophyceae species are enticing interest among researchers working in the nanotechnology discipline, because of their diverse biological activities such as anti-inflammatory, antioxidant, anti-microbial, and anti-tumor. In the present study, the anti-cancer properties of Polycladia crinita extract and green synthesized P. crinita selenium nanoparticles (PCSeNPs) against breast cancer cell line (MDA-MB-231) and solid Ehrlich carcinoma (SEC) were investigated. Methods: Gas chromatography-mass spectroscopy examinations of Polycladia crinita were determined and various analytical procedures, such as SEM, TEM, EDX, and XRD, were employed to characterize the biosynthesized PCSeNPs. In vitro, the anticancer activity of free Polycladia crinita and PCSeNPs was evaluated using the viability assay against MDA-MB-231, and also cell cycle analysis by flow cytometry was determined. Furthermore, to study the possible mechanisms behind the in vivo anti-tumor action, mice bearing SEC were randomly allocated into six equal groups (n=6). Group 1: Tumor control group, group 2: free SeNPs, group 3: 25 mg/kg Polycladia crinita, group 4: 50 mg/kg Polycladia crinita, group 5: 25 mg/kg PCSeNPs, group 6: 50 mg/kg PCSeNPs. Results: Gas chromatography-mass spectroscopy examinations of Polycladia crinita extract exposed the presence of many bioactive compounds, such as 4-Octadecenoic acid-methyl ester, Tetradecanoic acid, and n-Hexadecenoic acid. These compounds together with other compounds found, might work in concert to encourage the development of anti-tumor activities.Polycladia crinita extract and PCSeNPs were shown to inhibit cancer cell viability and early cell cycle arrest. Concentrations of 50 mg/kg of PCSeNPs showed suppression of COX-2, NF-кB, VEGF, ki-67, Notch 1, and Bcl-2 protein levels. Otherwise, showed amplification of the caspase 3, BAX, and P53 protein levels. Moreover, gene expression of caspase 3, caspase 9, Notch 1, cyclin D1, NF-кB, IL-6, and VEGF was significantly more effective with PCSeNPs than similar doses of free extract. Conclusion: The PCSeNPs mediated their promising anti-cancerous action by enhancing apoptosis and mitigating inflammation, which manifested in promoting the total survival rate and the tumor volume decrease.